2011
DOI: 10.1111/j.1600-051x.2011.01758.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum cholesterol ratios and periodontal infection: results of the Health 2000 Survey

Abstract: This study does not provide evidence that unfavourable lipid composition can be considered as an important risk for periodontal infection in a general adult population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
0
20
1
Order By: Relevance
“…An association between periodontal infections and lipid metabolism has been suggested but not established. Although most recent investigations 1,10‐23 have demonstrated a positive relationship between the two entities, some have reported to the contrary 24‐26 . However, most of these studies 1,11,13‐17,19,20 have been conducted in patients with chronic periodontitis.…”
mentioning
confidence: 99%
“…An association between periodontal infections and lipid metabolism has been suggested but not established. Although most recent investigations 1,10‐23 have demonstrated a positive relationship between the two entities, some have reported to the contrary 24‐26 . However, most of these studies 1,11,13‐17,19,20 have been conducted in patients with chronic periodontitis.…”
mentioning
confidence: 99%
“…2,3,4,5 Hyperlipidemia, i.e., elevated serum lipid levels, is thought to cause imbalance in the production of highly reactive molecular species and antioxidant defenses, leading to increased OS and creating a proinflammatory state that predisposes subjects to infections. 1,6 Hyperlipidemia is a risk factor for atherosclerotic diseases by causing hyperactivity of white blood cells, 7 and this hyperactivity leads to an increase in production of reactive oxygen species (ROS) and lipid peroxidation. 8 In periodontal disease, the interaction between host immune response and pathogens stimulates cytokine expression and subsequently generates excessive ROS-derived radicals.…”
Section: Müge Lutfioğlu (A)mentioning
confidence: 99%
“…The interference of different serum lipid subfractions and periodontal infection has been reported by several researchers, 15,16,17 whereas others have reported either no connections 18 or limited connection. 6,19 Till date, a limited number of studies have separately reported the connection between increased OS and hyperlipidemia 11,20 and increased OS and periodontitis. 2,3,4 To the best of our knowledge, only one clinical-based study 11 examined OS parameters in patients with periodontitis with hyperlipidemia, and that study measured parameters systemically in blood serum, not locally in GCF or gingival tissue.…”
Section: Müge Lutfioğlu (A)mentioning
confidence: 99%
“…Studies on the relationship of periodontal disease and increased serum level of lipids have reported controversial results. Some reported positive correlation between these two entities, 5,8,13‐15 whereas others found no such correlation 16–19 . However, most of the studies focused mainly on the relationship of low density lipoproteins (LDL) and total cholesterol (TC) with periodontal parameters, but few of them assessing the relationship of high serum level of TG's and periodontal diseases 2,5,6,20 …”
mentioning
confidence: 99%